Análise da expressão dos genes APEX1, POLΒ, RAC1 e NFKΒ em portadores de anemia falciforme - Pereira, Jamilly Florêncio (2019)
Sickle cell anemia (SCA) is a hereditary hematological disease characterized by a point mutation in the beta globin gene, generating an abnormal hemoglobin called hemoglobin S (HbS), homozygous (HbSS). Treatment consists of continuous use of hydroxyurea (HU), which increases the concentration of Fetal hemoglobin (HbF). Literature reports point to a potential genotoxic effect of UH, which may increase the risk of gene instability in these patients. The APEX1 gene has different functions, acting to repair DNA single strand damage mainly induced by oxidation and regulating oxidative stress and various redox transcription factors. In this context, the aim of the present study was to evaluate the expression of APEX1, POLβ; NFκβ and RAC1, associated with laboratory data, treatment with UH and disease severity in patients with AF. This is a cross-sectional study of 98 adult patients with PA, using HU and without HU, in outpatient follow-up at Walter Cantídio University Hospital (HUWC) and a control group of 28 healthy individuals (HbAA). Epidemiological, hematological and biochemical data were obtained from the analysis of medical records. APEX1, POLβ gene expression; RAC1 and NFκβ were performed in peripheral blood by quantitative real-time polymerase chain reaction (qPCR) using TaqMan® probes. Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS) version 21 software, with a significance level of 5% (p <0.05). The mean age of the patients was 32 (18-32) years, 59 (60.2%) females and 39 (39.8%) males. UH induced macrocytosis, reduction in leukocyte and neutrophil count and hemolysis parameters. Similar findings were found when stratifying patients in relation to HbF. By analyzing the expression of APEX1 POLB, RAC1 and NFKB genes regarding the use or not of HU, we observed a significant reduction of APEX1 and RAC1 expression in patients who did not use HU. Patients not using UH had lower levels of RAC1 expression when compared to patients treated with doses of 500mg / day. Patients treated with higher doses of HU had higher levels of POLB gene expression. Patients with HbF <15% had the highest levels of RAC1 gene expression and higher NFKB gene expression in Hb ≥25%. The POLB and RAC 1 (p <0.001, R = 0.1760) and NFKB and POLB (p <0.001 and R = 0.1730) genes correlated positively and moderately in patients with AF. A greater expression of APEX1 and POLB genes was observed in patients with the most severe form of the disease, the RAC1 gene was more expressed in mild form and an increase in NFKB gene expression in the intermediate form of the disease. The results show that AF patients have abnormalities in the expression of genes related to base excision repair (BER) APEX1 and POLB, and genes related to oxidative stress and inflammation such as RAC1 and NFKB genes. Regarding the use of UH, the drug may possibly be contributing to the worsening of genomic instability in the disease. However, further studies on the action of these genes are needed to assess their role in PA.